Soviet veterans of the Second World War a popular movement in an authoritarian society 1941-1991 - Edele, Mark (Oxford University Press, 2008)
The first book-length study of Soviet veterans of the Second World War and their movement. Based on extensive research in Soviet archives and libraries, it analyses the fate of the millions who returned from the war with Germany.